2020
DOI: 10.21608/mjcu.2020.93984
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Propolis Against Thioacetamide Induced Hepatorenal Injury in Adult Male Rats. Kidney Injury Molecule-1 (KIM-1) a Biomarker of Renal Injury

Abstract: Background: Thioacetamide (TAA), a known industrial toxic agent, is extensively used in animal studies for induction of hepatic necrosis, fibrosis and cirrhosis, also reported to be nephrotoxic through induction of oxidative stress. Propolis, bee glue, is known by its antioxidant and anti-inflammatory properties. Aim of Study: This work aimed to evaluate the potential protective effect of propolis on TAA-induced hepatorenal damage and to evaluate the efficacy of Kidney Injury Molecuole-1 (KIM-1) in early detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In previous research, TAA increased collagen deposition and induced glomerular sclerosis and necrosis with interstitial fibrosis [ 2 , 42 , 43 ]. Juxtamedullary collagen content increased significantly in the TAA treated group in this study which agreed with Mansour et al [ 10 ] who showed significant increase in the amount of collagen fibers in-between renal tubules and around renal glomeruli after TAA treatment as well. Moreover, significantly increased collagen and fibrin deposition in the renal medulla with focal mesangial cell proliferation and outstanding hepatic perivascular and peri-biliary deposition of collagen were noticed as well in the TAA supplemented group [ 26 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In previous research, TAA increased collagen deposition and induced glomerular sclerosis and necrosis with interstitial fibrosis [ 2 , 42 , 43 ]. Juxtamedullary collagen content increased significantly in the TAA treated group in this study which agreed with Mansour et al [ 10 ] who showed significant increase in the amount of collagen fibers in-between renal tubules and around renal glomeruli after TAA treatment as well. Moreover, significantly increased collagen and fibrin deposition in the renal medulla with focal mesangial cell proliferation and outstanding hepatic perivascular and peri-biliary deposition of collagen were noticed as well in the TAA supplemented group [ 26 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…Light microscopic examination of kidney tissue related to TAA intraperitoneally supplemented rats in a dose of 50 mg/kg/day, 5 days/week for 2 weeks showed glomerular and peritubular congestion with disruption of tubular epithelial lining and intra-luminal hyaline cast. Tubular cells showed vacuolations, Karyorrhexis and deeply stained nuclei [ 10 ]. Also, desquamation and loss of the tubular brush border with cell swelling, cytoplasmic vacuolations and pale cytoplasm were observed after single intraperitoneal injection of 200 mg/kg TAA in mice [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations